Enabling people with communication and cognitive impairments to provide feedback on service satisfaction: development and reliability testing of an adapted pictorial questionnaire. (2nd July 2020) - Clarkson, Katrina; Stokes, Lynne Turner; Sacchett, Carol; Ashford, Stephen
Abstract : Introduction/aims: Evaluation of patient satisfaction with health services is mandatory within the UK, but patients with communication difficulties are often excluded by their inability to complete written questionnaires. This study examines the test–retest reliability and agreement of an adapted, pictorial patient satisfaction questionnaire, based on the Talking Mats technique. Methods: A total of 26 participants, who had a range of communication impairments resulting from brain injury, completed two questionnaires while in specialist rehabilitation: a standard written and adapted pictorial questionnaire, at two time points to evaluate test–retest reliability. Agreement between the two questionnaire formats was also examined. Results: Test–retest reliability in overall scores between Time 1 and 2 was substantial for both the adapted pictorial questionnaire ( k =0.72 [95% confidence interval 0.388, 0.76]) and the standard written questionnaire (ϰ=0.78 [95% confidence interval 0.74, 0.82]). Overall agreement between the two techniques was ϰ=0.76 (95% confidence interval 0.73, 0.79). Eighty-six per cent of questions for patients with aphasia showed at least 'moderate' agreement between the two questionnaire types compared with only 67% in participants with cognitive communication disorder. Conclusions: The adapted pictorial questionnaire is a reliable tool for people with brain injury who have aphasia, enabling some patients to provide service satisfaction feedback who would have otherwise been excluded using a written questionnaire.